THE ROLE OF MOBILITY MANAGEMENT IN THE FIELD OF SUSTAINABLE DEVELOPMENT - Oksana Hulchak; Oleksandr Dziuba; Yevheniia Shapenko (Дороги і мости, 2022)
Introduction. In the past, the concept of transport was considered a very simple type of movement, but the corresponding update of this occurred with the advent of innovations in the field of transportation with the ability to transport people and goods with high productivity. First, the use of steam, and then gasoline and electricity, especially in the railway sector, changed the perception of mobility “manually” to “mechanized”. In the 20th century, the proliferation of the private car led to a revolution in mobility, a change in previous settings of the urban concept and its functionality. In the 1950s, the vast majority of the population could easily buy a private car, especially thanks to decisive political strategies that contributed to the development of the automotive industry. Mobility is a complex system that includes several modes of transport, such as road, rail, sea and air, interacting with the infrastructure through transport services. Man is between two entities, both user and object, depending on goals, potential benefits, or external factors.